Coach Education Programs for Professional Coaches in Finland - Lahtinen, J. (3rd International Forum on Elite Sport. Burleigh Court, Loughborough University, 9-11 September 2003, 2003)
Powerpoint-Präsentation zu den Möglichkeiten der professionellen Trainerausbildung am Sportinstitut Vierumäki (Finnland)